The Difficulties of the Students of IAI As’adiyah Sengkang in Mastering English - Bunyamin, Bunyamin (INTERACTION: Jurnal Pendidikan Bahasa, 2020)
This research objective is to describe the difficulties of the students in mastering English Preliminary observations in IAI As’adiyah Sengkang indicate that the English ability of the students is varied. The researcher limited this research in the second semester students of English Education Program of IAI As’adiyah Sengkang as participants of the research. The researcher focused in the difficulties of the students in mastering English. There are Two Difficulties discussed. They are the difficulties of the students in speaking and the difficulties of students in grammar. The researcher used descriptive qualitative research in this research. The technique of collecting the data in this research is in the form of interviews. The interviews provided questions that on the difficulties of students in mastering English. Interview is the technique in getting evidence deeply to students. The result of the research proves that most of the students in the second semester of English education program of IAI As’adiyah Sengkang liked learning English. They have many reasons why they like learning English. Besides that, they consider that English speaking is difficult to be learnt. They have two main problems. Those are pronunciation and vocabulary. Most of students also have problems in learning grammar. They are difficult to understand the formula of the structure. They also have problems in understanding the tenses.